Penerapan Model Contextual Teaching Learning pada Pembelajaran Literasi Numerasi di SMPS IT Karakter Anak Shalih Padang - Haripamyu Haripamyu; Mawanda Almuhayar; Noverina Alfiany (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
By current global needs, students are expected to be able to adapt to a rapidly changing world and participate actively in society. Students must become lifelong learners who need reading literacy and numeracy literacy competencies. Literacy Numeracy, often called numeracy, can be interpreted as the ability to apply mathematical concepts and skills to solve practical problems in everyday life. Starting in 2021, this ability will be measured through the Minimum Competency Assessment (AKM) aimed at classes V, VIII, and XI. The aim is to obtain information about the quality of a school so that it becomes a basis for improving the learning process in that school, especially concerning students' numeracy and literacy abilities. The problem faced by the Shalih Children's Character IT SMPS (KAS) is a lack of guidance on students' numeracy literacy skills needed to take AKM. Therefore, the Service Team from the Department of Mathematics and Data Science felt it necessary to carry out service at SMPS IT KAS as a continuation of the guidance that had been carried out in the previous year. The method used is to apply the Contextual Teaching Learning model, which helps teachers link learning material with real life and encourages students to connect their knowledge with application in everyday life. It is hoped that implementing this service can help teachers guide students in preparing for AKM in the following year.